Differential dry mass accumulation in eucalypt and pine exposed to glyphosate - Silva, Natálye Ramos da (2015)
The weed control onto planting line by using glyphosate is commonly used in forestry areas of eucalyptus and pine; however it can expose the crop of interest to herbicide drift and cause impact on the initial growth of plantlets. The objective was to evaluate comparatively the dry mass of eucalyptus and pine plants exposed to doses of glyphosate and to verify the occurrence of hormesis. In early transplanted plants, glyphosate herbicide was sprayed at doses varying from 0 up to 720 g ae ha-1, and the dry mass of stem, leaves, and shoot were evaluated at 30 days after spraying. Pine showed less susceptibility for dry mass of stem (occurring hormesis), while eucalyptus showed less susceptibility for dry mass of leaves (occurring hormesis). Hormesis occurred in pine and eucalyptus shoots at doses of 8 g ae ha-1 (4.1%) and 11 g ae ha-1 (4.8%), respectively; the dose required to reduce shoot dry mass by 50% was 75 g ae ha-1 and 108 ae ha-1, and the reduction of shoot dry mass was 57% and 69% (with plant death) when plants were exposed to glyphosate at 720 g ae ha-1, respectively for pine and eucalyptus. Pine is more susceptible to glyphosate than eucalyptus.